The Influence of Artificial Intelligence and Electronic Word of Mouth (eWOM) on Consumer Purchasing Decisions - Saleh, Farrel Alfarabi (Syntax Literate, 2025)
This study aims to analyze the effect of using artificial intelligence (AI) algorithms and electronic word of mouth (eWOM) on consumer purchasing decisions on the TikTok social media platform, with a focus on fashion products in the Greater Jakarta area. This study focuses on Generation Z and Millennials as the research population. This study used a quantitative approach with a survey involving 358 active respondents who met the criteria. The research model examines the relationship of variables such as Purchase Duration, Product Recommendation, Social Media Dependency, and Consideration Set, as well as the impact of eWOM on purchasing decisions. The results showed that Product Recommendation and Social Media Dependency have a significant influence on Consideration Set, which in turn influences consumer purchasing decisions. On the other hand, Purchase Duration does not have a significant influence on Consideration Set in the context of fashion purchases through TikTok. In addition, perceived eWOM was found to play an important role as an external factor that directly influences purchasing decisions. These findings provide insights for fashion industry players and digital platforms to optimize AI and eWOM-based marketing strategies, to increase consumer engagement and drive purchase decisions in the social media era.